1990
DOI: 10.1093/ptj/70.7.443
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Clinical Measurements of Forward Bending Using the Modified Fingertip-to-Floor Method

Abstract: The purpose of this study was to examine the intratherapist and intertherapist reliability of measurements obtained with a modified version of the fingertip-to-floor method of assessing forward bending. With the modified fingertip-to-floor (MFTF) method, patients stand on a stool and forward bend so that measurements can be taken on patients who are able to touch the floor or reach beyond the level of the floor. Randomly paired physical therapists took repeated MFTF measurements on 73 patients with low back pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
10

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 6 publications
0
67
0
10
Order By: Relevance
“…Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings. Clinical studies have found the reliability of the FTFD ranging from low [31] to high [4,15,19,39]. In our study, the relationship between structural changes of the lumbar spine and the FTFD was only weakly correlated to endplate changes on level L4-5.…”
Section: Mobility Testsmentioning
confidence: 49%
See 1 more Smart Citation
“…Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings. Clinical studies have found the reliability of the FTFD ranging from low [31] to high [4,15,19,39]. In our study, the relationship between structural changes of the lumbar spine and the FTFD was only weakly correlated to endplate changes on level L4-5.…”
Section: Mobility Testsmentioning
confidence: 49%
“…The modified Schober and the FTFD were described previously [4,15,19,27,31,39]. For the LB, the participants were told to slowly bend from the upright position to the side with their hand running down a vertical ruler.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…They were instructed to reach as far as possible with their fingertips toward the floor, with knees fully extended. 19 The results were measured in centimeters (negative values reflecting an inability to reach the stool and positive values reflecting the ability to reach beyond the level of the stool).…”
Section: Clinical Field Testsmentioning
confidence: 99%
“…For example, noninvasive methods comprise the inclinometer technique, 1,2 Schober technique, 3 modified Schober technique, 4 fingertip to floor method, 5,6 or skin-mounted optical or electromagnetic measuring devices. 7,8 Nevertheless, it has been shown that external measurement may not reflect the true intervertebral movement, and limitations have already been reported when measuring single segmental movement.…”
mentioning
confidence: 99%